Smartphone Addiction among Married Postgraduate Students - Shittu, Abdullateef; Bolaji, Hameed Olalekan (Bumi Publikasi Nusantara, 2023)
Smartphones have revolutionized the way individuals communicate, obtain information and pass the time in contemporary culture. The study investigates the effect of smartphone addiction on the marital relationship of married postgraduate students of Al-Hikmah University Ilorin, Kwara State. A cross-sectional research design approach was selected for the study. Al-Hikmah University Ilorin Postgraduate student was used as the population with 30 married postgraduate student couples using a non-probability convenience sampling technique. The research instrument used was the Smartphone Addiction Scale (SAS) to assess the impact of smartphone addiction on the marital relationship of married postgraduate students of Al-Hikmah University. The demographic data of the participants were analyzed using frequency and percentage. Data collected were analyzed using mean, Pearson product-moment correlation (PPMC), Degree of Freedom, Standard deviation and P-value to answer both the research questions and hypotheses were tested at 0.05 level of significance. There was a significant relationship between smartphone addiction marital relationship of married postgraduate students. The present study revealed that a large number of people are addicted to smartphones. The study also revealed that there was a significant relationship between smartphone addiction and its impact on the marital relationship of postgraduate students. The study concluded that there was a significant relationship between smartphone addiction and the marital relationship of postgraduate students of Al-Hikmah University.